2016
DOI: 10.1186/s13054-016-1223-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting cardiorespiratory instability

Abstract: This article is one of ten reviews selected from the Annual Update in Intensive Care and Emergency medicine 2016. Other selected articles can be found online at http://www.biomedcentral.com/collections/annualupdate2016. Further information about the Annual Update in Intensive Care and Emergency Medicine is available from http://www.springer.com/series/8901.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…For example, support vector machines have been used in noninvasive estimates of simulated and actual hemorrhage severity [100,101], though it should be noted that these models were used to separate 2-3 classes of severity rather than have a continuous output and were also not individual-specific. Other studies have utilized random forest, support vector machines, k-nearest neighbors and neural network algorithms to model risk of cardiorespiratory instability in the hospital through integrated monitoring systems [102][103][104]. K-nearest neighbors, random forest, gradient boosted trees and logistic regression with L2 regularization were used to classify hypotensive events in time series data from the ICU [105].…”
Section: Integrationmentioning
confidence: 99%
“…For example, support vector machines have been used in noninvasive estimates of simulated and actual hemorrhage severity [100,101], though it should be noted that these models were used to separate 2-3 classes of severity rather than have a continuous output and were also not individual-specific. Other studies have utilized random forest, support vector machines, k-nearest neighbors and neural network algorithms to model risk of cardiorespiratory instability in the hospital through integrated monitoring systems [102][103][104]. K-nearest neighbors, random forest, gradient boosted trees and logistic regression with L2 regularization were used to classify hypotensive events in time series data from the ICU [105].…”
Section: Integrationmentioning
confidence: 99%
“…One team from Pittsburgh in the United States has already developed, validated, and tested real-time intraoperative risk prediction tools based on electronic health record data and high-fidelity physiological waveforms to predict cardiopulmonary instability in the intensive care unit. 111 More recently, another team from London developed the "Artificial Intelligence Clinician" to learn optimal treatment strategies for sepsis in intensive care. 112 The authors demonstrated that using their "Artificial Intelligence Clinician" allowed better treatment selection which could lead to lower mortality rates in patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…A combination of more information sources together (i.e., pulse transit time, finger volume clamp, and surface sensor) may further improve the way we perform hemodynamic monitoring. For instance, taking together more vital signs (like the Vital Sign Index by Visensia™ monitor, OBS Medical, IN-USA) may help to predict cardiac instability ( 51 ) or assessing the heart rate variability from electrocardiography may be useful in predicting hypotension ( 52 ). Another example may be the recently approved Hypotension Probability Indicator by Edwards Lifesciences Inc. which should be able to predict hypotension based on analysis of multiple domains including arterial pressure curve complexity, heart rate variability, and others by proprietary algorithm combined with machine learning.…”
Section: Emerging and Future Conceptsmentioning
confidence: 99%